PENERAPAN METODE SAFETY FIRST CRITERION PADA SELEKSI SAHAM UNTUK PEMBENTUKAN PORTOFOLIO OPTIMAL - HAKMI, HAMITA; DHARMAWAN, KOMANG; WIDIASTUTI, RATNA SARI (E-Jurnal Matematika; Vol 12 No 2 (2023), 2023)
The formation of an optimal portfolio can be done with the Safety First Criterion method which is based on down side risk, namely the risk of causing a loss. The purpose of this study is to determine the optimal portfolio using Safety First Criterion method. Safety first criteria for portfolio selection are concerned only with the risk of failing to achieve a criteria minimum target return or secure prespecified safety margins. There are three criteria for the Safety First, namely Roy, Kataoka and Telser criteria. The results of this study formed an optimal portfolio with different risk values the Roy criteria is 0.0486, Kataoka is 0.0487 and Telser is 0.0527. So that the best portfolio of the three criteria is Roy's criterion because it has the lowest risk value with expected return the same .